Hybrid Learning-Based Educational Game Frog to Improve Speaking Skills - Siti Fatimah Zahra; Andi Syahputra Harahap (International Journal of English and Applied Linguistics (IJEAL), 2023)
The educational game Frog is implemented with a hybrid learning model to improve the speech skills of pre-schoolers. This type of research uses Research and Development (R&D) with a Four-D (4D) development model. The research development adopts the 4D model of the figures of Thiagarajan, et al, namely: define, design, develop, and disseminate. The research subject focuses on preschool children group B (aged 5-6 years) as the object of research. The data collection technique used expert validation questionnaires, observations, and tests to measure learning outcomes against the media. The usefulness of research answers learning to improve children's speech so they grow into active and confident children. This hybrid learning-based frog educational game is designed to simulate existing problems so that essence or knowledge can be obtained that can be used to solve these problems. The results from media experts get a percentage of 78%, including the valid category and material experts get 89% in the beneficial type. Students' and teachers' responses to the frog educational media based on hybrid learning on speaking skills are fascinating. This can be seen from the small group trial, with a percentage of 84% and the field group, with a rate of 82%. The effectiveness of the hybrid learning-based frog educational game learning media on speaking skills in speaking skills with IK (an indicator of success) is 87.5%.